Miconia macuxi (Miconieae, Melastomataceae): a new species from the Amazonian white sand vegetation - Meirelles, Julia; Caddah, Mayara Krasinski; Goldenberg, Renato (Phytotaxa, 2015)
Miconia macuxi is described from the states of Roraima and Amazonas, in northern Brazil, and Atabapo and Amazonas, in southern Venezuela. It occurs in white sand vegetation, and can be recognized by the strongly discolorous leaves with dense stellate trichomes on their abaxial surfaces, secund inflorescences, petal margins with glandular-stipitate trichomes, and white stamens, the antepetalous with the connective with two ventral lobes and a dorsal tooth.